(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
The study was conducted to identify the major reproductive health problems and its associated risk factors in indigenous Borena breed cows in Borena zone in Southern Ethiopia between September 2013 and February 2014. Out of the total 409 cows examined, 195 (47.7%) were having at least one of the reproductive problems identified by either questionnaire interview (n=329) or regular follow up (n=80) of individual cows. The major reproductive health problems identified in the present study were mastitis (21.3%; n=87/409), abortion (12.2%; n=50/409), repeat breeder (10.3%; n=42/409), anestrus (10.3%; n=42/409) and retained fetal membrane (RFM; 7.6%; n=31/409). The rate of abortion increased significantly (p=0.001) with the increase in the stage of gestation. Laboratory findings indicated that brucellosis and mastitis had great roles in reproductive health problems of dairy cows in the study area with prevalence rates of 2.91% and 68.41%, respectively. In conclusion, the study revealed that several reproductive health problems such as mastitis, abortion, repeat breeder, anestrus and RFM are mostly prevalent in dairy cows in Borena zone in southern Ethiopia. http://dx.doi.org/10.5455/javar.2014.a32